Genotypic and phenotypic features of dyslipidemia in a sample of pediatric patients in China - Qianwen Zhang; Guoying Chang; Yijun Tang; Shili Gu; Yu Ding; Yao Chen; Yirou Wang; Shijian Liu; Jian Wang; Xiumin Wang (BMC, 2023)
Abstract Background Dyslipidemia, especially hypercholesterolemia is of significant clinical interest. Precise diagnosis is not paid enough attention to about the management of pediatric patients with hypercholesterolemia, which is especially apparent in China. Given this, we designed this study to confirm the specific molecular defects associated with hypercholesterolemia using whole-exome sequencing (WES) to be helpful for precise diagnosis and treatment. Methods Pediatric patients were enrolled using specific criteria and their clinical information were recorded for later evaluation in conjunction with the WES completed for each of these patients. Results Our criteria allowed for the initial enrollment of 35 patients, 30 of whom (aged 1.02-12.99 years) underwent successful genetic sequencing and clinical investment. Positive results were obtained in 63.33% (19/30) of these patients. We identified 25 variants in 30 pediatric patients with persistent hypercholesterolemia, seven of them were novel and variants in LDLR and ABCG5/ABCG8 ranks first and second, respectively. Further analysis revealed that the levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (ApoB) and lipoprotein (a) were higher in patients with positive genetic results. Conclusion Our study enriched the genetic and phenotypic spectra for hypercholesterolemia in young patients. Genetic testing is important for the prognostics and treatment of pediatric patients. Heterozygous ABCG5/8 variants may be underestimated in pediatric patients with hypercholesterolemia.